Blue Ti3+ self-doped TiO2 nanosheets with rich 001 facets for photocatalytic performance. (19th March 2019) - Zhen, Deshuai; Gao, Chan; Yang, De; Zhu, Xingqi; Grimes, Craig A.; Liu, Yu; Cai, Qingyun
Abstract : The as-prepared BT1.5 TNs exhibits superior photocatalytic performance for RhB degradation due to Ti 3+ doping. Abstract : Novel blue Ti 3+ self-doped TiO2 nanosheets (BTTNs) with rich 001 facets of 26.4% were synthesized by a modified solvothermal process, and they were characterized in detail by XRD, TEM and Raman spectroscopy, which show that Ti 3+ was successfully doped into anatase TiO2, increasing the number of 001 facets. UV-vis analysis shows profound absorption in the visible region and the bandgap energy of B1.5 TTNs is 2.86 eV, which is remarkably smaller than that of pure anatase TiO2 (3.2 eV). Due to the low bandgap energy and high reactivity of the 001 facets, high photocatalytic activity was achieved. Under simulated solar light irradiation for 70 min, 99% rhodamine B was degraded and successfully detected by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS).